2009
DOI: 10.1097/shk.0b013e3181a47f85
|View full text |Cite
|
Sign up to set email alerts
|

LIVER X RECEPTOR AGONIST GW3965 DOSE-DEPENDENTLY REGULATES LPS-MEDIATED LIVER INJURY AND MODULATES POSTTRANSCRIPTIONAL TNF-α PRODUCTION AND P38 MITOGEN-ACTIVATED PROTEIN KINASE ACTIVATION IN LIVER MACROPHAGES

Abstract: Modulation of the host inflammatory response to infection may be a key approach to improve the outcome of patients with sepsis and organ injury. We previously reported that pretreatment of rats with the liver X receptor (LXR) agonist GW3965 reduced the liver injury associated with endotoxemia and attenuated the production of TNF-alpha by rat Kupffer cells. Here, we examine the dose-dependent effect of GW3965 on liver injury and cytokine production in a rat model of endotoxemia and explore the mechanisms underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 28 publications
1
25
0
1
Order By: Relevance
“…We and others have reported that LXR protects against lipopolysaccharide (LPS)-induced tissue injury, demonstrating protective effects on the liver and the lung [22,30]. Against this background, we hypothesized that LXR could be a node in the complex regulation of the pathogenesis of polymicrobial sepsis.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…We and others have reported that LXR protects against lipopolysaccharide (LPS)-induced tissue injury, demonstrating protective effects on the liver and the lung [22,30]. Against this background, we hypothesized that LXR could be a node in the complex regulation of the pathogenesis of polymicrobial sepsis.…”
Section: Discussionmentioning
confidence: 94%
“…This may be attributable to differences in the models and how the agonist was given. In the endotoxemia model [22,23], agonist and LPS were given intravenously, and monocytes and liver Kupffer cells were exposed rapidly. Plasma TNF-a release is an early event with a relatively short time-frame in this model.…”
Section: Lxr Protects From Clp Liver Injury 285mentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that ABCA1 is important for apolipoprotein A-I/TTP pathway-mediated post-transcriptional control of inflammatory cytokine mRNA decay [23]. Additionally, there is an abundance of evidence indicating that LXR agonist inhibits MAPK superfamily activation both in vitro and in vivo [24,25]. In the light of these data, we hypothesized that LXR activation could promote TTP expression and TTP-mediated inflammatory cytokine mRNA decay.…”
Section: Introductionmentioning
confidence: 99%
“…In some cell types, LXR activation inhibits ERK1/2 and p38 MAPK signaling pathways [24,25]. To verify whether LXR activation also inhibits these two signaling pathways in LPS-stimulated THP-1 macrophages, western blot analysis was carried out for phosho-ERK1/2 and phosho-p38 MAPK.…”
Section: Lxr Activation Inhibits Erk/p38 Signaling Pathwaymentioning
confidence: 99%